Henry and Mudge and the Great Grandpas - Cynthia Rylant (India Simon Spotlight, 2006)
Henry (and of course Mudge) loves to visit Great Grandpa Bill. He lives in a house with a lot of other granpas who like to play with a little boy and his dog. But when Henry discovers a swimming pond near the granpas' house, he finds out how much fun the grandpas really can be.
Keywords: F&P-IR-J4 -- F&P-IR-J4